EVALUATION AND KEY CONCEPTS OF FEMINIST LITERARY THEORY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This article examines the theoretical foundations and key concepts of feminist literary theory as a critical approach to the interpretation of literary texts. Feminist criticism focuses on the representation of women in literature, the construction of gender roles, and the power relations embedded within literary discourse. The study analyzes the historical development of feminist literary theory, highlighting its major schools and methodological principles. Particular attention is given to concepts such as patriarchy, gender identity, female voice, and the re-evaluation of the literary canon from a feminist perspective.